2021
DOI: 10.1108/imds-02-2021-0093
|View full text |Cite
|
Sign up to set email alerts
|

Social media influencers, product placement and network engagement: using AI image analysis to empirically test relationships

Abstract: PurposeThis research tests empirically the level of consumer engagement with a product via a nonbrand-controlled platform. The authors explore how social media influencers and traditional celebrities are using products within their own social media Instagram posts and how well their perceived endorsement of that product engages their network of followers.Design/methodology/approachA total of 226,881 posts on Instagram were analyzed using the Inception V3 convolutional neural network (CNN) pre-trained on the Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 64 publications
2
16
1
5
Order By: Relevance
“…In addition to testing the mediating effect in this study, a moderating effect was also identified to find out whether the negative publicity that celebrities have when they are exposed to a scandal will have an impact on consu mers' purchase intentions for brands endorsed by these celebrities. Previous research identified an influence on consumer engagement and brand loyalty (Osei-Frimpong et al, 2019, Rutter et al, 2021. However, there are some differences between this study and previous research.…”
Section: Introductioncontrasting
confidence: 63%
“…In addition to testing the mediating effect in this study, a moderating effect was also identified to find out whether the negative publicity that celebrities have when they are exposed to a scandal will have an impact on consu mers' purchase intentions for brands endorsed by these celebrities. Previous research identified an influence on consumer engagement and brand loyalty (Osei-Frimpong et al, 2019, Rutter et al, 2021. However, there are some differences between this study and previous research.…”
Section: Introductioncontrasting
confidence: 63%
“…The influence of the celebrity's trustworthiness on consumers' purchase intention has been shown in previous research (Erdogan, 1999;Till and Busler, 2000), indicating that celebrities' ability to influence purchase behaviour hinges on the perceived credibility and genuineness of the endorsement (Rutter et al, 2021). So, the following hypothesis is presented:…”
Section: Credibility Of Celebritiesmentioning
confidence: 81%
“…Therefore, consumers get more easily influenced by celebrities perceived as authentic and to whom they trust. Similarly, prior research reports that the influence of celebrities through social media is due in part to their increased authenticity, as they are perceived as a more authentic source compared to celebrities who appear in traditional advertising (Rutter et al, 2021).…”
Section: Credibility Of Celebritiesmentioning
confidence: 96%
See 1 more Smart Citation
“…It also enables organizations to understand and rapidly respond to the market's evolving needs. Organizations desire to achieve the full potential of social media engagement (SME) to improve their sales, customer satisfaction and opportunity in decision quality (Rutter et al ., 2021; Simon and Tossan, 2018). Hence, it becomes crucial for the business to maintain its social presence through media content (Gandhi and Kar, 2022).…”
Section: Introductionmentioning
confidence: 99%